Meningkatkan Aktivitas dan Hasil Belajar Tematik Siswa Kelas II SDN Kasreman 01 Geneng melalui Model Teams Games Tournament (TGT) - Tama, Fidya Nurhuda Sukma; Maharani, Swasti; Andayani, Tutik Sulistyo (LP. Ma'arif Janggan Magetan, 2023)
The purpose of this study is to determine the increase in thematic learning activities and outcomes of grade 2 students of SDN Kasreman 01 Geneng through the application of the Teams Games Tournament (TGT) learning model. The implementation of this research is carried out through general steps, namely 1) class precentation, 2) learning in groups (teams), 3) games (games), 4) tournaments (tournaments), and 5) group awards (teams reception). This research uses two types of data, namely quantitative data and qualitative data. Quantitative data in the form of learning outcomes are analyzed in a percentage descriptive manner while qualitative data in the form of observations of student activities are analyzed qualitatively with interactive analysis techniques then interpreted based on calculations and compared with established indicators. The success indicators of this PTK are, the activeness of students in learning activities at least 75%, learning outcomes or the number of students who get scores according to KKM (>70) at least 75%. The results of the study obtained from the assessment of the learning outcomes of grade II students in the first cycle were: (1) an average grade of 71.00 with classical learning completeness of 73.33%; (2) the average student activity is 71.61%. Cycle II is: (1) grade average 77.60 with classical learning completeness of 93.33%; (2) the average student activity is 81.11%. Based on the results of the study, it was concluded that the TGT learning model can improve Thematic learning activities and outcomes in grade II students at SDN Kasreman 01 Geneng